Dinosaurs and prehistoric life. - DK Publishing, Inc.; Smithsonian Institution (New York, NY DK Publishing, 2019)
The stunning visuals and authoritative text make Dinosaurs and Prehistoric Life a fascinating and revealing encyclopedia that will appeal to the whole family. From the origin of life, through the age of dinosaurs stalked by the terrifying Tyrannosaurus rex, to the earliest humans, this book tells the story of life on Earth. Dinosaurs may be the stars of the show, but the book is truly comprehensive, with fossil plants, invertebrates, amphibians, fish, birds, reptiles, mammals, and even early bacteria conjuring up an entire past world. To put all of these extinct species in context, the book explores geological time and the way life-forms are classified. It also looks at how fossils preserve the story of evolution, and how it can be deciphered. The chapter on "Young Earth" explains how forces shaped Earth and steered the course of life. The main part of the book - "Life on Earth" - lays out and catalogues the rich story of life, from its beginnings 4 billion years ago, through each geological period, such as the Jurassic and Cretaceous, to the present. The stunning visuals and authoritative text make Dinosaurs and Prehistoric Life a fascinating and revealing encyclopedia that will appeal to the whole family.
Young earth. Exploring earth's past ; The origin of the earth ; The first 500 million years ; Plate tectonics ; Changing climates ; Life and evolution ; Classification ; Mass extinctions ; Types of fossils ; Information in the fossil record ; Key fossil sites ; The geological timescale -- Life on earth. Archean ; Proterozoic ; Cambrian ; Ordovician ; Silurian ; Devonian ; Carboniferous ; Permian ; Triassic ; Jurassic ; Cretaceous ; Paleogene ; Neogene ; Quaternary.
Includes index.
"The definitive visual guide to prehistoric animals" -- Cover.
"Content previously published as Prehistoric life in 2009"--Title page verso.
108517
Keywords: Dinosaurs; Animals, Fossil; Evolution (Biology); Plants, Fossil; Fossil hominids; Prehistoric peoples; Paleobiology; Earth (Planet) -- Origin; Encyclopedias